Amb a 1-immunostimulatory Oligodeoxynucleotide Conjugate Immunotherapy Increases CD4+CD25+ T Cells in the Nasal Mucosa of Subjects with Allergic Rhinitis - Kazuhisa Asai; Susan C Foley; Yuki Sumi; Yasuhiro Yamauchi; Naoya Takeda; Martin Desrosiers; Francois Lavigne; Qutayba Hamid (Allergology International, 2008)
[Background]:We have previously shown that short-course treatment with Amb a 1-immunostimulatory phosphorothioate oligonucleotide conjugate(AIC)before the ragweed season modifies the response of the nasal mucosa to allergen challenge in ragweed-sensitive patients by increasing Th1 cytokines and decreasing both Th2 cytokines and eosinophilia after the ragweed season. The effect of AIC immunotherapy on CD4+CD25+ T cell expression in the nasal mucosa is unknown. [Objective]:To determine the in vivo effect of short-course AIC immunotherapy on CD4+CD25+ regulatory T cells in the nasal mucosa of ragweed-sensitive subjects. [Methods]:19 ragweed-sensitive patients with allergic rhinitis were randomly assigned to receive either 6 escalating doses of AIC(0.06-12μg；n＝12)or placebo(n＝7)at weekly intervals immediately before the 2001 ragweed season. Nasal biopsies were taken at baseline prior to immunization and again post immunization 24 hours after ragweed allergen challenge at the start and end of the ragweed season. The expression of T regulatory cells, IL-10 and TGF-β was assessed at each time point by immunohistochemistry. [Results]:The numbers of allergen-induced CD4+-, CD4+CD25+-, IL-10- and TGF-β-positive cells in the nasal mucosa after AIC immunization before the ragweed season did not differ between the two groups. Repeat challenge after the ragweed season led to a significant increase in CD4+CD25+ cells in AIC-compared with placebo-treated subjects. A trend toward an increase in IL-10-positive cells in the AIC-treated group did not reach statistical significance. [Conclusions]:Short-course AIC immunotherapy increases CD4+CD25+ regulatory T cell infiltration in the nasal mucosa following allergen challenge after seasonal ragweed-pollen exposure.